Implementasi Pasal 32 UU No. 11 Tahun 2008 tentang Perlindungan Data Pribadi dalam Transaksi Fintech - Aditya Sulistyo Budhi; Widi Nugrahaningsih; Ety Isworo (Journal of New Trends in Sciences, 2025)
The misuse of personal data in financial technology (fintech) services, particularly in peer-to-peer lending practices, is showing a worrying upward trend and is an urgent legal issue that requires addressing. Article 32 of Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) serves as a primary legal basis for protecting electronic data. However, the effective implementation of this article in the context of fintech services still faces various challenges. This study employed an empirical legal approach with a combination of literature study and interviews. Interviews were conducted at the Surakarta Financial Services Authority (OJK) Office and with a number of fintech service users as respondents. The results showed that approximately 70% of personal data misuse cases originated from illegal online lending services. The most frequently reported violations included unauthorized use of data (40%), access to contacts and galleries on personal devices (35%), and threats of personal data dissemination (25%). The main obstacles in implementing Article 32 of the ITE Law include the difficulty of tracking perpetrators' jurisdiction, technical limitations in digital forensics, and low public legal literacy. Therefore, policy integration with Law Number 27 of 2022 concerning Personal Data Protection and the Financial Services Authority (OJK) provisions in POJK No. 77/POJK.01/2016 is necessary. This study recommends strengthening regulations, establishing an independent supervisory authority, increasing public education, and utilizing digital technology to promote more effective personal data protection in the Indonesian fintech ecosystem.